O ensino de cinemática através de atividades recreativas na quadra de esportes - Amaral Neto, Domingos Alves do (2019)
In this paper, a didactic sequence for the teaching of kinematics through recreational activities in the school sports court is presented with the objective of achieving a more meaningful learning from the effective participation of the students. Using sports as a motivating factor and based on the ideas of constructivism, a didactic sequence was made interspersing classes that involved explanatory moments in the classroom (theoretical component) and recreational moments in the sports court (practical component). The theoretical classes were focused on situations that occur in sports, while the practical classes, for the making of videos and the application of the concepts studied in the classroom. The theoretical component consisted of lectures and analyses of videos recorded in practical classes, which involved measurements, runs, throws and ball kicks. Sporting materials were used as resources besides measuring tape, timers and video cameras for video analyses. This videos were recorded on the court with the students' participation in the various activities proposed. For each activity, a video analysis was performed using the Tracker program, which generates several possibilities to approach the content, since it allows the creation of graphs and the observation of each movement in detail. Finally, during the presentation of the video analyses, some conceptual doubts were corrected and the knowledge was consolidated. The students' return exceeded expectations, as they felt they were agents of the teaching-learning process, participating in all stages of knowledge construction.